Effects of body mass index and gender on left atrial size in Chinese hypertensive patients - Xi Chen; Meifang Wu; Kaizu Xu; Meinv Huang; Haishan Xu (Clinical and Experimental Hypertension, 2020)
Background Left atrial enlargement (LAE) is a common cardiac structural change in patients with hypertension, and obesity could further promote LAE. However, little is known about the effect of overweight on left atrial size, and if there is a gender difference of the effect. The aim of this study was to analyze the effects of different body mass index (BMI) grades (normal weight, overweight, and obesity) on left atrial size in both male and female patients with hypertension. Methods A total of 710 patients with hypertension were divided into 3 study groups: normal weight group (BMI < 24 g/m2, n = 302), overweight group (24 kg/m2 ≤ BMI < 28 kg2, n = 318), and obesity group (BMI ≥28 kg/m2, n = 90). The clinical data, echocardiographic indexes and left atrial size were obtained from all the subjects. Pearson correlation analysis was used to analyze the correlation between clinical variables and left atrial diameter (LAD)/left atrial diameter index (LADI), and stepwise regression evaluation was used to study the relevant factors affecting LAD/LADI among all patients, male and female patients for possible gender difference. Results The significant difference in LADI was noted in the three study groups with obesity group of 23.96 ± 2.90 mm/m, overweight group of 22.50 ± 3.02 mm/m and normal weight group of 21.08 ± 2.80 mm/m, respectively (P < . 05). After adjusting for age and gender, there was still significant difference in LADI among the three groups (P < . 05). The correlation between BMI and LADI was higher than that between systolic blood pressure (SBP) and diastolic blood pressure (DBP) (r = 0.348 vs 0.092 and −0.068, respectively, P < .05). After adjusting for other influencing factors, there was still a significant correlation between BMI and LADI (β = 0.326, P < .001), but no correlation was found between SBP and DBP (P > .05). For each additional unit of BMI, LAD increased by 0.034 mm and LADI increased by 0.305 mm/m. Multiple linear regression analysis showed that BMI, left ventricular mass index (LVMI), age and female gender were independently correlated with LADI (P < .05). And BMI was the most significant influencing factor of LADI in male patients (β = 0.350, P < .001), followed by LVMI (β = 0.343, P < .001). While in female patients, LVMI was the most significant (β = 0.353, P < .001), followed by BMI (β = 0.302, P < .001). Conclusion Overweight and obesity were significantly associated with LAE in hypertensive patients, with obesity more significant than overweight. While BMI had the greatest correlation with LAE in male, LVMI was the most important determinant of LAE in female. Therefore, in addition to weight loss, more attention should be paid to early inhibition of left ventricular remodeling in female with hypertension.